Consolidation Efficiency of Natural and Plastic Geosynthetic Band Drains. Issue 4 (2001) - Jang, Y.S.; Kim, Y.W.; Park, J.Y.
Abstract : Consolidation efficiency of natural and plastic geosynthetic band drains is examined using laboratory tests and a three-dimensional numerical flow model. The numerical model is first validated by comparing its results with the laboratory consolidation data and then the influence of the drain installation depth on the consolidation time is estimated. The drains used in the analysis are circular and band-shaped natural drains and a band-shaped plastic drain. The results of discharge capacity tests show that the discharge capacity of the plastic drain is larger than those of the natural drains. Despite the difference in discharge capacity of the plastic and natural geosynthetic drains, the degree of consolidation versus time relationships obtained from laboratory consolidation tests were similar and the numerical model predicted the consolidation behavior quite well. The numerical simulation results of the effect of installation depth showed that the degree of consolidation versus time relationship for the circular-shaped natural and plastic geosynthetic drains was not significantly influenced by increases in installation depth. However, the consolidation-time relationship for the band-shaped natural geosynthetic drain, having a smaller discharge capacity, was influenced by well resistance with increased installation depth.